THE EFFECT OF PERSONALITY, SELF-CONTROL AND FINANCIAL CONSTRAINTS ON FINANCIAL PLANNING - Nurul Huda; Novita Indrain; Tyas Widy Cahyanti; Yuli Asmawati; Triska Oktaviani (Journal of Management and Entrepreneurship Research, 2020)
Objective: Small and medium enterprises (SMEs) have become a focus of attention by economists until now. Furthermore, their financial planning capacity as reflected in the level of their financial literacy in Central Java province which is 33.51% and this is included in the not-literate category. This paper describes the results of a study investigating the effect of personality, self-control, and financial constraints on SME financial planning in Jepara, Central Java. Research Design & Methods: A quantitative approach is used to determine the effect of personality, self-control, and financial constraints to financial planning by using using software SmartPLS. This study used 285 questionnaires collected from SME owners in Jepara by proportional random sampling. The sample size was determined using the Slovin formula. Measurement of variables was done by the adoption of indicators of previous studies by adjusting it according to current situation. Findings: The results showed that personality, self-control, and financial constraints have a positive and significant effect on financial planning. The positive personality shown by SME owners and their ability to control emotions have a positive impact on the financial planning process. These findings also indicate that financial constraints are not an obstacle for SMEs to remain productive and conducting future financial planning. Implications & Recommendations: SME owners can use the results of this study as they are more enthusiastic to increase productivity. SMEs must begin to develop financial planning in more detail to improve business performance and maintain themselves in the market. Future research can re-examine the concept of this research on a larger scale, nationally or even internationally. Contribution & Value Added: This research contributes to social and financial literature because it involves personality in the financial planning process.